Computation of the Normalized Prediction Error of the Electroencephalogram Signal - Chaofeng Cai; Yong Zhang; Jingying Ren; Liying Jiang (Institute of Advanced Engineering and Science, 2012)
In this paper, the normalized prediction error of the electroencephalogram (EEG) signal recorded at five different mental tasks was computed. The results indicate that there exists predictability in the EEG signal beyond the baseline prediction of the mean and the one-step-ahead normalized prediction error of EEG signal vary greatly when different mental tasks are implemented, which implies that the one-step-ahead normalized prediction error can be employed as a feature of EEG signal to distinct different mental tasks. For different subjects, the one-step-ahead normalized prediction error vary greatly even the EEG signal are recorded from the same electrode under the same mental task, which implies that the subjects’ individual differences should be considered adequately when the one-step-ahead normalized prediction error is employed to distinct different mental tasks. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1268